2017
DOI: 10.1097/nor.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Noise Reduction to Reduce Patient Anxiety During Cast Removal

Abstract: Utilizing noise reduction headphones and a personal electronic device during the cast removal process decreases patient anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…Studies demonstrating the influence of using earplugs on anxiety are limited in the literature. Mahan et al 20 used earphones on children to reduce noise during the removal of casts and concluded that the use of earphones reduced anxiety. This conclusion is in line with that of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrating the influence of using earplugs on anxiety are limited in the literature. Mahan et al 20 used earphones on children to reduce noise during the removal of casts and concluded that the use of earphones reduced anxiety. This conclusion is in line with that of our study.…”
Section: Discussionmentioning
confidence: 99%
“…17 Studies have reported that the use of earplugs, especially in noisy environments, increase sleep quality and duration and reduce delirium, agitation and anxiety. 18,19 Mahan et al 20 placed earphones on patients to reduce noise during the removal of casts and determined that anxiety was reduced in this way.…”
Section: Introductionmentioning
confidence: 99%
“…The 8 included studies evaluated the impact of interventions that included noise reduction [17,20,23], the inclusion of other specialists (play therapist, child life therapist) [24,25], electronic tablets for distraction [21], preparatory sensation vs. procedural-based information [18,19], and music therapy [22] (Table 2). Two interventions outlined the use of theory in developing the intervention [18,19,25].…”
Section: Interventionsmentioning
confidence: 99%
“…Five evaluated psychologically-based interventions [18,19,21,22,24,25]; employing the strategies of distraction [21,24,25], preparatory information [18,19], music therapy [22], and play [24,25], alone or in combination. One study used both physical and psychological approaches, combining the strategies of noise reduction and distraction (Table 2) [23]. Wong [25] Theory: Theory of stress and coping (Lazarus and Coleman [29]).…”
Section: Interventionsmentioning
confidence: 99%
“…Periode tidur yang lebih lama berhasil dicapai untuk pasien dari kelompok intervensi dengan harga yang sangat efektif (masing-masing £ 2,50). Menurut Mahan et al (2017) menggunakan earphone pada anak-anak untuk mengurangi kebisingan selama pelepasan gips dan menyimpulkan bahwa penggunaan Earphone atau Earplug dapat mengurangi kecemasan. Menurut, Koo dan Koh (2008) efek dari alat pelindung mata (Eyemask) dan penutup telinga (Earplug) pada gangguan tidur pada pasien CCU adalah cara yang sederhana dan murah untuk meningkatkan kualitas tidur pasien di CCU (Coronary Care Unit).…”
Section: Pembahasan Efektivitas Pemakaian Eyemask Dan Earplugunclassified